The use of Software Tools in Solving some Mathematical Problems - Z.U. Tursinboyeva; Z.T. Ismоilova (Zien Journals, 2022)
This article presents recommendations for combining the concepts of physics and computer science in teaching mathematics.
Keywords: Calculate work; pump; elementary work; additivity